1970
DOI: 10.1083/jcb.47.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Transitional Cardiac Cells of the Conductive System of the Dog Heart

Abstract: Cardiac cells with distinctive electrophysiological and morphological features were found at the junctional region between Purkinje and ventricular cells of the dog heart . The electrophysiological exploration of these "transitional" cells revealed action potentials markedly different in configuration from those generated by Purkinje or by ventricular cells . The impaled cardiac cells which generated transitional action potentials were identified in serial sections and studied with the light and the electron m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

1972
1972
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…The present results give additional support to the interpretations advanced by several authors (HOFFMAN and CRANEFIELD, 1960;SANO et al, 1964;MATSUDA et al, 1967;BENITEZ, 1967, 1970;MARTINEZ-PALOMO et al, 1970) in regard of the mechanisms responsible for the delays that appear in certain regions of the mammalian heart and in the cold blooded species (SHINOZAKI, 1942;INOUE, 1959 ;KANNO, 1963 ;TSUJI, 1963 ;IRISAWA et al, 1965). We have shown that in the axolotl and turtle hearts there are limited regions in which the propagation of impulses is delayed.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The present results give additional support to the interpretations advanced by several authors (HOFFMAN and CRANEFIELD, 1960;SANO et al, 1964;MATSUDA et al, 1967;BENITEZ, 1967, 1970;MARTINEZ-PALOMO et al, 1970) in regard of the mechanisms responsible for the delays that appear in certain regions of the mammalian heart and in the cold blooded species (SHINOZAKI, 1942;INOUE, 1959 ;KANNO, 1963 ;TSUJI, 1963 ;IRISAWA et al, 1965). We have shown that in the axolotl and turtle hearts there are limited regions in which the propagation of impulses is delayed.…”
Section: Discussionsupporting
confidence: 79%
“…junctional region differ in fine structural features from adjacent fibers, particularly as to diameter, the quantity of myofibrils and the distribution and number of specialized intercellular junctions. Moreover, in an earlier paper (MARTINEZ-PALOMO et al, 1970) it was reported that in the dog heart there are cells located between the Purkinje and ventricular fibers which generate transitional potentials markedly different in configuration from those originated in the Purkinje or ventricular cells. These junctional cells have some distinguishing cytological characteristics that, according to the electrical theory, may determine the slow rate of conduction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The localization of lanthanum in the outer leaflets of plasma membranes of frog nerve fibers was first reported by Doggenweiler and Frenk (4) . In addition, lanthanum used as colloidal suspensions (19) or in ionic form (7,15,16) acts as an electron-opaque tracer of the extracellular space . Revel and Karnovsky (19) used colloidal lanthanum to identify a previously undetected 20 A intercellular space at the gap junctions of mouse heart and liver ; we later obtained similar findings in a variety of epithelial and myocardial tissues (13,15,16) .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, lanthanum used as colloidal suspensions (19) or in ionic form (7,15,16) acts as an electron-opaque tracer of the extracellular space . Revel and Karnovsky (19) used colloidal lanthanum to identify a previously undetected 20 A intercellular space at the gap junctions of mouse heart and liver ; we later obtained similar findings in a variety of epithelial and myocardial tissues (13,15,16) . Colloidal lanthanum has also been used to stain certain components of the surface of embryonic (9,10,14,21) and differentiated cells (22) .…”
Section: Introductionmentioning
confidence: 99%